The accreditation project for the Batna Faculty of Medicine in Algeria: opportunities, challenges and prospects - Guedjati, Mohamed Ridha; Benaldjia, Hanane; Bouhidel, Jalaleddinne Omar; Taibi, Adeila Dallel (Technium Social Sciences Journal, 2025)
In the current context of increasing internationalization of higher education, academic leaders have had to mobilize their decision-making and consultative bodies at various levels of intervention and mediation. The aim of this approach is to establish a quality assurance system to manage the university's transition from an academic to a professional status in terms of quality. To achieve this, a fundamental change is required. This involves a shift from a "supply logic" to a "need logic." Algerian medical faculties are thus obliged to align themselves with this evolution. In the field of health sciences education, quality assurance is striving to comply with international standards. These standards are part of the accreditation process for medical faculties. The Batna medical school has made accreditation one of its priorities, and the process was initiated in May 2024. The standards of some accrediting bodies are well documented and meet basic universal criteria. The aim of this work is to document the opportunities, challenges and prospects encountered in drawing up the self-analysis report on the Batna Medical School's accreditation project.